Management of suicidal risk in the emergency department: A clinical pathway using the computerized adaptive screen for suicidal youth - Jacqueline Grupp‐Phelan; Adam Horwitz; David Brent; Lauren Chernick; Rohit Shenoi; Charlie Casper; Michael Webb; Cheryl King; Pediatric Emergency Care Applied Research Network (PECARN) (Journal of the American College of Emergency Physicians Open)
Abstract Objective Given the critical need for efficient and tailored suicide screening for youth presenting in the emergency department (ED), this study establishes validated screening score thresholds for the Computerized Adaptive Screen for Suicidal Youth (CASSY) and presents an example of a suicide risk classification pathway. Methods Participants were primarily from the Study One derivation cohort of the Emergency Department Screen for Teens at Risk for Suicide (ED‐STARS) enrolled in collaboration with Pediatric Emergency Care Applied Research Networks (PECARN). CASSY scores corresponded to the predicted probabilities of a suicide attempt in the next 3 months and risk thresholds were classified as minimal (<1%), low (1%–5%), moderate (5%–10%), and high (>10%). CASSY scores were compared to risk thresholds derived from clinical consensus and ED complaints and dispositions. CASSY risk thresholds were also examined as predictors of future suicide attempts in the Study Two validation cohort of ED‐STARS. Results A total of 1452 teens were enrolled with a median age of 15.2 years, 59.5% were female, 55.6% were White, 22% were Black, 22.3% were Latinx, and 42.8% received public assistance. The clinical consensus suicide risk groups were strongly associated with the CASSY‐predicted risk thresholds. Suicide attempts in the Study Two cohort occurred at a frequency consistent with the CASSY‐predicted thresholds. Conclusions The CASSY can be a valuable tool in providing patient‐specific risk probabilities for a suicide attempt at 3 months and tailor the threshold cutoffs based on the availability of local mental health resources. We give an example of a clinical risk pathway, which should include segmentation of the ED population by medical versus psychiatric chief complaint.